THE ROLE OF WAKAF IN REALIZING PEOPLE'S WELFARE - Tina Arfah (AL-ITTIFAQ: Jurnal Ekonomi Syariah, 2023)
Poverty is one of the many problems in this country. Various efforts have been made by the government and elements of society so that the problem of poverty in this country can be resolved. Some attempts were successful, some were not. Poverty that occurs in society is not entirely the responsibility of the government, but is a shared responsibility between the government and the community. is to manage waqf productively. This research is related to the potential of waqf as a development for the welfare of the community. This research is a qualitative research and uses library research (Library Research). The data sources in this study consisted of primary data and secondary data. The primary data sources in this study were the book by Mannan, M. Abdul, Cash Waqf Certificate A, Islamic Financial Instruments and Mustafa E. Nasution's book “Islamic Financial Innovation Cash Waqf. that waqf in Indonesia has an annual economic potential of IDR 3 trillion. The potential is extraordinary, especially if the funds are handed over to the manager and invested in a productive sector, for example, the funds are deposited in an Islamic bank, in other words, every year Islamic banks provide 9% Profit Sharing, then at the end of the year there will already be funds of IDR 270 Billion. The benefits of cash/cash waqf are not only able to increase economic growth, but also to create income distribution.Keyword: Cash Waqf, Welfare, Empowerment Public